In Search of Lost Time : Examining the Duration of Sudden Stops in Capital Flows - David, Antonio; Goncalves, Carlos Eduardo (Washington, D.C. : International Monetary Fund, 2019)
This paper investigates what factors affect the duration of sudden stops in capital flows using quarterly data for a large panel of countries. We find that countries with floating exchange rate regimes tend to experience shorter sudden stop episodes and that fixed exchange rate regimes are associated with longer periods of low output growth following sudden stops. These effects are quantitatively large: having a flexible exchange rate regime increases the probability of exiting the sudden stop state by between 50 to 80 percent. Flexible exchange rate regimes significantly shorten the duration of output decelerations following sudden stops by over 30 percent. Positive variations in terms of trade also abbreviate the duration of sudden stops. In terms of policies, identification is trickier, but the evidence suggests that monetary policy tightening shortens the duration of sudden stops. Changes in capital account restrictions do not seem to matter.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet